Facilitating the enhancement of lecturer academic performance based on the SINTA platform - Sutha, Diah Wijayanti; Ramadhan, Kadar (Universitas Muhammadiyah Magelang, 2025)
Increasing citations and h-index are important indicators in assessing lecturer academic performance, which contributes to the reputation of higher education institutions. This community service activity aims to enhance the understanding and skills of lecturers and educational staff in optimizing strategies to increase citations and h-index through the Science and Technology Index (SINTA) platform. This activity was conducted in the form of a webinar using the Zoom Meeting application. The webinar included materials on scientific work promotion strategies, SINTA profile management, and academic metric enhancement techniques. Evaluation results showed an average increase in participant understanding of 37%. Participants also provided positive feedback on the relevance of the materials and the implementation methods. This activity had a direct impact on improving digital and academic literacy of lecturers, which has the potential to enhance the quality of scientific publications and institutional accreditation.